2019
DOI: 10.3897/rrpharmacology.5.39681
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions in the psychiatric hospital: Frequency analysis

Abstract: Citation: Kirilochev OO, Dorfman IP, Umerova AR, Bataeva SE (2019) Potential drug-drug interactions in the psychiatric hospital: Frequency analysis. Research Results in Pharmacology 5(4): 1-6. https://doi. AbstractIntroduction: Drug-drug interactions are an important clinical problem in pharmacotherapy. This study is focused on different types of drugs used in a psychiatric hospital. Materials and methods:The pharmacoepidemiological study included the analysis of medical records of 500 psychiatric inpatients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…Other authors, by contrast, have only dealt with subsets of MRPs in psychiatric inpatients, such as drug–drug interactions. For instance, Kirilochev and colleagues found that 77.2% of psychiatric inpatients (386/500) were affected by potential drug–drug interactions, 22 which is comparable to the figures detected in our study (84.3% and 36.5% of patients affected by pharmacodynamic and pharmacokinetic drug interactions, respectively). Of note, the patients in the Kirilochev et al.…”
Section: Discussionsupporting
confidence: 90%
“…Other authors, by contrast, have only dealt with subsets of MRPs in psychiatric inpatients, such as drug–drug interactions. For instance, Kirilochev and colleagues found that 77.2% of psychiatric inpatients (386/500) were affected by potential drug–drug interactions, 22 which is comparable to the figures detected in our study (84.3% and 36.5% of patients affected by pharmacodynamic and pharmacokinetic drug interactions, respectively). Of note, the patients in the Kirilochev et al.…”
Section: Discussionsupporting
confidence: 90%
“…[ 17 ] DDIs between olanzapine and haloperidol are known to increase the risk of developing EPS. [ 28 ] Other studies have documented most common pDDIs between haloperidol and trihexyphenidyl (72 [5.3%]),[ 21 ] amitriptyline and fluoxetine (24.5%),[ 22 ] and antipsychotics and beta-blockers. [ 29 ] The difference in these findings could be due to divergences in the study setting, duration, and mainly the study population included.…”
Section: Discussionmentioning
confidence: 99%
“…documented the number of medications as the most significant predictor of DDIs in patients with mild dementia,[ 34 ] while other studies reported predictors such as prescribed medications,[ 22 ] race and female sex,[ 28 ] and patient's age. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Превалирование потенциальных "Serious" и "Monitor Closely" межлекарственных взаимодействий между соматическими препаратами у пациентов старше 65 лет, по всей видимости, связано с наличием сопутствующей патологии в пожилом возрасте и, как следствие, изменением фармакологической структуры лекарственных препаратов, участвующих во взаимодействиях. Зафиксированные данные в целом коррелируют с результатами, полученными нами в исследовании, в котором применялся другой инструмент по выявлению нерациональных комбинаций -Drug Interaction Checker интернет-ресурса drugs.com, информация в котором согласована с официальными инструкциями к лекарственным препаратам, утверждёнными Food and Drug Administration (FDA) [16].…”
Section: материалы и методыunclassified